2016
DOI: 10.5812/ijhrba.24169
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Type II Diabetic Patients With Healthy People: Coping Strategies, Hardiness, and Occupational Life Quality

Abstract: BackgroundDue to the epidemiologic transition and a rise in the prevalence of non-communicable diseases different coping strategies have been studied and developed. These strategies may help the affected people to conduct a normal life style.ObjectivesThis research was conducted in Qazvin, Iran to determine the relationship between coping strategies, hardiness, and occupational life quality in Type II diabetic patients and healthy people.Patients and MethodsQuestionnaires such as Valton’s on “occupational life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…Finally, denial and positive reframing predicted the total CLDQ-NAFLD in diabetics, while denial, active coping and self-blame did in obese. Our results therefore revealed that an active coping style, focused on action (active coping, positive reframing or acceptance), was associated with better QoL in diabetics and obese people, in line with other studies [ 15 , 18 ]. On the contrary, a passive/avoidance coping style (denial, self-blame, self-distraction or disengagement) was related to greater decline, mainly in the mental QoL, of these patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, denial and positive reframing predicted the total CLDQ-NAFLD in diabetics, while denial, active coping and self-blame did in obese. Our results therefore revealed that an active coping style, focused on action (active coping, positive reframing or acceptance), was associated with better QoL in diabetics and obese people, in line with other studies [ 15 , 18 ]. On the contrary, a passive/avoidance coping style (denial, self-blame, self-distraction or disengagement) was related to greater decline, mainly in the mental QoL, of these patients.…”
Section: Discussionsupporting
confidence: 92%
“…Studies disagree about whether these metabolic pathologies are associated with more use of active coping strategies [ 14 , 15 ], or passive/avoidance [ 16 , 17 ]. The relevance of this issue stems from active coping usually predicting better global QoL in both diabetics and obese than avoidance coping [ 15 , 18 ]. The same trend is observed in chronic hepatic patients [ 19 ], although for the moment there are no results available for NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…In the diabetic group, the number of occupational-financial stressful factors and environmental factors was significantly higher among men than women, and this is in agreement with the results of other studies (16). Based on the results of Mann-Whitney test, the total number of stressful life events among diabetic elderly was significantly higher than those among non-diabetic elderly (P > 0.05), which is in line with the findings of other studies (17). Therefore, it can be claimed that the most prominent effect of stressful factors has been on diabetic patients, and it is probably the high frequency and high intensity of such factors that cause the development of diabetes in elderly adults.…”
Section: Discussionsupporting
confidence: 79%
“…This causes great physical and mental pain to the patient, and using this method for a prolonged period has poor tolerance and compliance to the treatment. 4 Therefore, researchers are pursuing for a better way to mimic the body's pancreas for feedback and balance, an intelligent system that automatically controls the release of insulin by sensing stimuli produced by changes in the body's blood sugar concentration. [5][6][7] The glucose-sensitive drug delivery system can adjust the release of insulin according to the change in human blood glucose concentration.…”
Section: Introductionmentioning
confidence: 99%